A Case of Intestinal Obstruction in Pregnancy Diagnosed by MRI and Treated by Intravenous Hyperalimentation. (24th November 2016) - Daimon, Atsushi; Terai, Yoshito; Nagayasu, Yoko; Okamoto, Atsuko; Sano, Takumi; Suzuki, Yusuke; Kanki, Kazuyoshi; Fujita, Daisuke; Ohmichi, Masahide
Abstract : Intestinal obstruction in pregnancy is rare and is mainly caused by prior pelvic surgery. We herein report a case of intestinal obstruction in a pregnant female with a history of laparoscopic myomectomy, who presented with hypogastric pain, abdominal distension, and vomiting at 26 weeks of gestation. A simple intestinal obstruction was diagnosed by MRI. Conservative treatments, including intravenous hyperalimentation and the placement of an ileus tube, were provided and her abdominal symptoms improved for 14 days. After restarting oral intake, she had no abdominal symptoms. She gave birth to a 2, 146 g female infant by caesarean section at 37 weeks and 1 day of gestation. Although an area of cicatrization, which was thought to have been the starting point of the occlusion that caused the intestinal obstruction, was found, the excision of the small intestine was not necessary. Her postoperative course was uneventful. Intestinal obstruction requires a prompt diagnosis and aggressive intervention may be necessary to minimize the morbidity and mortality associated with this rare complication of pregnancy. MRI can be safely used during pregnancy to diagnose intestinal obstruction and intravenous hyperalimentation may improve the maternal and fetal prognoses.